Kinetics of Optical Properties of Colorectal Muscle During Optical Clearing - Carneiro, Isa (2018)
In this paper, we describe a simple and indirect method to evaluate the kinetics of the optical properties for biological tissues under optical clearing treatments.We use the theoretical formalism in this method to process experimental data obtained from colorectal muscle samples to evaluate and characterize the dehydration and refractive index matching mechanisms.